The Effect Of Employee Relations And Compensation On Turnover Intention: The Mediating Role Of Work Stress Among Pt. Bank Mandiri Employees In Mataram City - Ainnun Zahriahtun; Muttaqillah (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study examines the influence of employee relations and compensation on turnover intention, with work stress as a mediating variable among 67 employees of PT. Bank Mandiri in Mataram City, addressing retention challenges in Indonesia's banking sector where turnover rates exceed national averages. Employing a quantitative causal-associative design, data were collected through validated questionnaires and analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS). The findings reveal that employee relations exert a strong negative effect on turnover intention (β = −0.624, p < 0.05), while compensation demonstrates a strong positive effect on work stress (β = 0.857, p < 0.05) but no significant direct impact on turnover intention (β = 0.150, p > 0.05). Notably, work stress neither significantly affects turnover intention (β = −0.092, p > 0.05) nor mediates the relationships between employee relations and turnover intention or compensation and turnover intention. The model explains 75.4% of work stress variance but only 40.8% of turnover intention variance. These results underscore that high-quality workplace relationships serve as the primary retention driver, suggesting organizations should prioritize enhancing supervisor communication, peer collaboration, and conducive work climates over salary adjustments alone. Theoretically, this research extends Social Exchange Theory within Indonesian banking contexts while revealing limitations of stress-based pathways in explaining turnover. Practically, findings emphasize leadership development and mentoring initiatives as cost-effective retention strategies. Future research should employ longitudinal designs and incorporate additional mediators to explain the remaining variance in turnover intention.